Impact of Pesticide Exposure on Farmer Metabolism Systems : A Systematic Review - Triyani; Hanifa Maher Denny; Suroto (Masters Program in Public Health, 2025)
Background: Farmers are informal sector workers exposed to multiple health risks due to the unsafe use or storage of pesticides. Farmer are at high risk of pesticide poisoning, which can affect their metabolic disorders. This review aims to systematically examine the impact of pesticide exposure on health disorders in farmers’ metabolic systems. Subjects and Method: This was a systematic review using the PICO model. The keywords used for the search for the study were “Impact” and “Pesticide” AND “Exposure” AND “Farmers’” AND “Metabolism System” in various databases. The inclusion criteria in this study were studies discussing variables, research articles, and articles published from 2021 onwards, while the exclusion criteria were articles that do not have access or are not full-text. Data were collected using the extraction form, which includes PICO, and assessed using the PRISMA diagram. Data analysis was done descriptively by comparing the research results. Results: The study found that pesticide exposure can affect the metabolic system, potentially damaging cells and causing oxidative stress by damaging lipids, proteins, and DNA, leading to genetic mutations and cell degeneration. The impact of exposure to glyphosate and arsenic pesticides causes liver and kidney function damage and decreased cardiovascular health. Exposure to paraquat, glyphosate, and oxyfluorophene causes Thyroid Cancer. Exposure to organophosphate and organochlorine pesticides causes Parkinson’s. Insecticides, herbicides, and fungicides cause sleep disorders. In addition, herbicide pesticides have a significant relationship with type 2 diabetes. Conclusion: Based on research findings, pesticide exposure impacts farmers’ metabolic systems, including the incidence of Chronic Kidney Disease, decline in cardiovascular health, Thyroid Cancer, Parkinson’s Disease, Sleep Disorders, and Type 2 Diabetes.